Deliverable 1.10 Roadmap for a sustainable Arctic Observing System - Sandven, Stein; Sagen, Hanne; Hamre, Torill; Buch, Erik; Pirazzini, Roberta; Gustavsson, David; Beszczynska-Möller, Agnieszka; Voss, Peter; Danielsen, Finn; Iversen, Lisbeth; Caumont, Herve; Ottersen, Geir; et al. (Science of The Total Environment, 2022)
The INTAROS Roadmap describes the way forward to improve and sustain the observing capacity in the Arctic. The Roadmap addresses the full data delivery chain from observing sensors to data repositories with focus on in situ observations. The document describes key factors determining how well an observing system can function in the Arctic, involving technological advances, infrastructure and data networks. Furthermore, the document emphasize the importance of cross disciplinary collaboration and stakeholder engagement as part of the data delivery chain. The development of in situ observing systems in the Arctic, especially ocean-based observations in the ice-covered regions, depends heavily on mature technology, transport infrastructures and logistical services allowing personnel to access the areas. Deployment and operation of observing platforms require use of icebreakers, aircraft, manned ice stations and automated systems that can operate year-round Based on the experience and knowledge of the INTAROS consortium, the following recommendations are formulated: The importance of in situ observations must be promoted as the backbone for building knowledge about climate and environmental change in the Arctic, at the same level as satellite observations and modelling systems The funding mechanisms for in situ observing systems need to be strengthened and coordinated between programmes, projects and institutions involved in Arctic observation, including local communities The Joint Statement of Ministers (ASM 2021), signed by 25 countries and six Indigenous Peoples organizations, states that they agree to strengthen cooperation on implementing Arctic observing and data sharing, implying that they need to allocate resources for in situ measurements contributing to the observing systems. Technology development for more robust and reliable in situ observing systems is needed. Here, major industry actors can play a role by investing in platforms and sensors that can operate autonomously in the Arctic The data delivery ...